Analysing the dimensions of value ascribed to learning by Malaysian teachers using a learning value scale. - Norliza Kushairi (Penerbit Universiti Kebangsaan Malaysia, 2012)
Rapid changes in educational settings place pressure on teachers to update their professional knowledge and skills, which can be accomplished by their participation in continuous professional development (CPD) programmes. The notion that teachers are true lifelong learners implies that they should hold positive attitudes and values needed to excel in learning. However, information on how teachers value their learning is sparse. This paper examines the dimensions of value placed on learning by teachers who undertook further learning as part of their CPD. As professionals, teachers are workers; therefore, their learning context is inevitably career-oriented. Thus, a Learning Value Scale questionnaire was developed by adapting Super’s Work Values Inventory proposed by Super and Neville (1986). The respondents were 599 teachers categorised into four groups—three groups engaged in different types of learning programmes (Undergraduate (UG), Postgraduate (PG), and Generic), and the control group did not participate in any learning activities. The responses were subjected to Principal Component Analysis. Results show that teachers see learning in four dimensions which are conceptually meaningful for, or associate with, the values of Achievement, Humanitarian Concern, Status, and Career Security. Examination of individual item responses across groups reveals that items for economic and job promotion show a distinct difference between the UG and Generic groups. In light of these findings, the study discusses the systemic cultural factors that conditioned the teachers’ concept of the value of learning. This baseline data can help teacher educators to understand teachers’ identity as learners. The findings also suggest that policy makers should review their learning policy initiative, and teachers as implementers of education should reflect on their own practice of learning.